Promotion Of Environmental Protection In Film: Case Study Of Documentary Film “Winter Fruits” - Prnjat, Dejana (The Turkish Online Journal of Design Art and Communication, 2016)
Documentary films, whether perceived as a creative treatment of actuality or as a tool for presenting life as it is, are becoming more attractive form to film artists. One of the reasons may be the fact that the documentary film is usually a smaller investment than the feature film, and that lately some of them generate quite high earnings, as the films Fahrenheit 9/11 and March of the Penguins. However, part of the charm of the documentary film is that it affects its audience differently than the feature film. Boundary line between the audience and the film almost disappears, and the audience becomes a witness. That is why the documentaries are often used for marketing purposes. Questions related to promotion of environmental protection more and more frequently attract the attention of the documentary film makers, as evidenced by the increasing number of environmental film festivals in the world. The main aim of this paper is to present one such film - Serbian low-budget documentary film Winter fruits. Powerful message this film carries, that we should all take care of the planet Earth since it is the only place we can live on, was recognized at film festivals worldwide. The film has won numerous awards, including the very prestigious Golden Dolphin, awarded at the Documentary Film Festival in Cannes in 2011, and the Grand Prix for the best ecotourism film, awarded by CIFFT (Comité International des Festivals du film Touristique) in Vienna 2011.
Keywords: Serbian documentary film Winter Fruits; promotion of environmental protection; film festivals; awards; Belgesel Film; Çevre koruma teşviki; film festivalleri; ödüller